The influence of social media marketing and electronic word of mouth (e-WOM) on purchase intention through brand image as a mediating variable - Fadhia Mey Aulia Qolbi; Dwi Cahyaningdyah (Universitas Nusa Cendana, 2026)
This study investigates the mediating role of brand image in the relationships between social media marketing (SMM), electronic word of mouth (EWOM), and purchase intention among skincare consumers in Central Java. As digital platforms are increasingly influencing consumers to make decisions in the beauty industry, understanding the mechanisms through which online marketing activities influence purchase intention has become a critical area of research. Employing a quantitative research from 175 social media users, from questionnaire distributed online using a convenience sampling technique. The data analysis used was SEM with SmartPLS. It was found that SMM and BI exert significant positive effects on PI, indicating that engaging digital marketing activities and favorable brand perceptions play important roles in encouraging consumers’ willingness to purchase skincare products. In contrast, EWOM does not directly influence PI. However, both SMM and EWOM significantly contribute to the formation of BI. Furthermore, the mediation analysis demonstrates that BI fully mediates the relationship between EWOM and PI and partially mediates the relationship between SMM and PI. These results suggest that consumers’ responses to online information and marketing communications are largely shaped through the development of positive brand perceptions. The study contributes to the digital marketing and consumer behavior literature by highlighting the strategic importance of BI as a key mechanism through which social media engagement and online consumer communications translate into stronger PI in the skincare industry. Keywords: Purchase Intention; Social Media Marketing; Electronic Word of Mouth; Brand Image